Maha mandapa in front of the garbhagriha - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple. The space in front of the garbhagriha (sanctum sanctorum) is the maha mandapa which is used as a congregation space and for conducting rituals. A pradakshina (circumambulation path) goes around the garbhagriha and the mahamadapa. Instead of the traditional shikhara, the temple was reconstructed with a dome by the Archaeology Department of the erstwhile Jaipur State in the 1940s.